2017
DOI: 10.7860/jcdr/2017/26845.9905
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin E and Vitamin A in Oral Mucositis Induced by Cancer Chemo/Radiotherapy- A Meta-analysis

Abstract: Introduction: Oral mucositis is known to hamper the quality of life in patients treated for oral cancer. Many pharmacological agents have been tried and tested in its management, especially vitamin supplements including A, E and their combinations.Aim: A Meta-analysis was carried out to evaluate the efficacy of vitamins individually used for prevention or treatment of oral mucositis separately for chemotherapy, concurrent chemo radiotherapy, radiotherapy and Haematopoietic Stem Cell Transplantation (HSCT) indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 13 publications
0
50
0
5
Order By: Relevance
“…Oral mucositis is a complicated adverse reaction during cancer treatment invariably affecting the outcome of the therapy. Radiotherapy-treated individuals have about 100% occurrence of oral mucositis compared to those with chemotherapy alone, which accounts for 40% (19). These unavoidable sequalae were the subject of various treatment strategies which yielded partial success.…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucositis is a complicated adverse reaction during cancer treatment invariably affecting the outcome of the therapy. Radiotherapy-treated individuals have about 100% occurrence of oral mucositis compared to those with chemotherapy alone, which accounts for 40% (19). These unavoidable sequalae were the subject of various treatment strategies which yielded partial success.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the possible positive effects of antioxidants for preventing radiation toxicity without a negative effect on tumor control. Some studies proposed the use of natural antioxidants such as beta carotene and vitamin E for preventing mucositis, melatonin for patients with brain cancer and a combination of some antioxidants for prostate cancer patients [89][90][91][92]. Studies concluded that with limited exceptions, administration of antioxidants does not interfere with tumor control [93].…”
Section: Flavonoids and Natural Antioxidantsmentioning
confidence: 99%
“…6,12,16 RT'nin neden olduğu OM semptomları KT'ye göre daha uzun sürmekte ve şiddetli olmaktadır. 32,33 Bu çalışmada, yalnızca RT alan hastalarda OM sıklığı daha yüksek bulunmasına rağmen anlamlı bir fark saptanmamıştır. Bu çalışmadan farklı olarak, Öhrn ve ark.…”
Section: Bulgularunclassified